Adaptive fuzzy PID control for servo motor direct-drive pump control system - Zheng, J.-M.; He, M.-J.; Liu, E.-D.; Yuan, Q.-L.; Xiao, J.-M.; Tang, A.-F. (Journal of Digital Information Management, 2014)
The direct-drive pump control system has been gradually applied to the industrial control field due to its high control precision, fast response, small throttle loss and compact structure. This paper adopts the fuzzy PID control method to resolve the hydraulic cylinder position servo control of direct-drive pump control system. The system model and fuzzy PID control algorithm was established by using AMEsim/Simulink joint simulation platform. The step response and Sine tracking performance of the system with PID and fuzzy PID control algorithms was investigated by simulation. At the same time, the performance of PID and fuzzy PID control was studied on the self-developed electro-hydraulic servo control experiment table. The results show that the adaptive fuzzy PID control can greatly improve the performance of the PID control, and has the characteristics of fast response, short rise time, small time delay and overshoot.
Keywords: Adaptive fuzzy PID control; AMESim/simulink; Direct-drive pump control system; Labview; Position servo control